Design and development of a solar energy system for AC and DC use in home - Lim, Willie Zhen Yi (Nanyang Technological University, 2020)
This report reviews a typical solar inverter and shows the process of designing a new solar inverter with space efficiency. Information on how an entire system that harnesses energy from sunlight will be included and respective data will be presented. The computation of the mathematical formula will be available, and the choice of components will be explained in this report. Designing of the circuit using EasyEDA and implementing it with results will be shown. Lastly, the integration of the entire subsystem will be implemented, and results are shown in this report.